Degree of hydrolysis, functional and antioxidant properties of protein hydrolysates from Grass Turtle (Chinemys reevesii) as influenced by enzymatic hydrolysis conditions. Issue 8 (24th June 2021) - Islam, Md. Serajul; Hongxin, Wang; Admassu, Habtamu; Noman, Anwar; Ma, Chaoyang; An wei, Fu
Abstract: Grass turtle muscle was hydrolyzed with papain enzyme to produce protein hydrolysate (PH) and the degree of hydrolysis (DH) was determined. Under optimal conditions, the highest DH was 19.52% and the yield was recorded as 17.26%. Protein content of the hydrolysates was ranged from 73.35% to 76.63%. Total amino acids were more than 96.77% for each PH. The PH obtained at DH 19.52% achieved excellent solubility and emulsifying activity which were 95.56% and 108.76 m 2 /g, respectively at pH 6. Foam capacity amounted 100% in PH of DH 19.52% at pH 2, and water‐holding capacity was 4.38 g/g. The antioxidant activity showed the strongest hydroxyl radical scavenging activity (95.25%), ABTS (84.88%), DPPH (75.89%), iron chelating (63.25%), and cupper chelating (66.90%) at DH 11.96%, whereas reducing power (0.88) at DH 19.52%. Thus, the findings indicated that utilization of grass turtle muscle protein hydrolysate is a potential alternative protein resource to improve the nutritional and functional properties in food ingredients and product formulations. Abstract : This is the first study using enzymatic hydrolysis to prepare protein hydrolysates from Grass Turtle. Degree of hydrolysis was clearly affected by enzymatic hydrolysis conditions. Enzymatic hydrolysis process led to improve Grass Turtle protein hydrolysate properties. The highest protein solubility was 95.56% at pH 6 in protein hydrolysate obtained at DH 19.52%.Antioxidant activities were affected by molecular weights and amino acid profiles of protein hydrolysate.